BIODAMAGE OF FUELS AND FACILITIES OF FUEL SUPPLY ENTERPRISES - Vovk, Yuliia; Matvyeyeva, Olena (Science-based technologies, 2023)
Actuality. The modern market of oil and oil products requires the creation and maintenance of fuel stocks at fuel supply enterprises in proper quality. This depends on the efficiency of rational storage and use of petroleum products, studying the possibilities of reducing the negative impact of physical and chemical processes that exist during the interaction of fuels with construction materials. Problem setting. Processes of corrosive destruction of materials as a result of chemical or electrochemical interactions between the material and the environment are an actual problem today. Fuel, in the composition of which harmful substances may appear during storage, causes a corrosive effect on the materials of the technological equipment during each stage of its life cycle. The goal of the work. Study of the mechanism of the influence of corrosive and biocorrosive factors on the deterioration of the quality of hydrocarbon fuels during their storage; impact on the operational condition of technological equipment. Research results. The result of the vital activity of microbiological contamination of fuels (bacteria, fungi) is the arrival of undesirable compounds, which contributes to a change in the pH of the fuel medium. This leads to increased corrosion of technological equipment. Also, the course of the fuel oxidation process is accompanied by the further formation of corrosion-active compounds. They lead to the destruction of the structural material and the formation of harmful compounds, which negatively affect the fuel quality indicators. Conclusions. Undoubtedly, the course of corrosion processes caused by the microbiological fuel factor has a negative effect on technological equipment and fuel quality. The mechanism of the course of corrosion processes in the fuel environment investigated in the work testifies to the presence of a biocorrosive factor in operational conditions that affects the deterioration of the quality of hydrocarbon fuels, especially during their long-term storage.